Religião e política em Minas Gerais : formas de ativismo cristão no poder legislativo e em controvérsias públicas - Vítor Corrêa Aleixo (2019)
This comparative research proposes to investigate the forms of Christian activism in the legislative power and in public controversies in Brazil, particularly in the state of Minas Gerais and in its capital Belo Horizonte. Amid a multifaceted and dynamic sociocultural, political and religious context, ecclesiastical and lay representatives from evangelical denominations were selected because of their expressive presence in the religious field of Minas Gerais and in the state and municipal legislative houses, Legislative Assembly of the State of Minas Gerais and Municipal Chamber of Belo Horizonte. The temporal cut starts from the 1980s, from the end of the military dictatorship and the beginning of the process of redemocratization to the present, with emphasis on the last legislatures in the state and municipal legislative power. The sample delimitation covers individual and collective actors from four distinct Christian confessions, Baptist Churches, Assemblies of God, Church of the Foursquare Gospel, and Universal Church of the Kingdom of God. The comparative approach is directed to a broad and diverse sample, since evangelical denominations differ due to contextual, institutional, doctrinal, relational, discursive and practical factors. Thus, the intention is to understand to what extent the confessional identity, the theological-ritualistic arrangement, the model of ecclesiastical government, the denominational political project and the socio-biographical trajectory influence the forms of Christian activism in the legislative power and in public controversies in the Minas Gerais and Belo Horizonte contexts. The consonances of strategies of electoral proselytism, media serving, investments in direct and indirect candidacies, insertions in the public space, ecclesial modulation of parliamentary acting, and interdenominational and supraparty alliances with the congregational and episcopal models of ecclesiastical government, sectarian and denominational organizations, historical and renewed Protestant, classical Pentecostal, Pentecostal of divine healing and Neo-Pentecostal matrixes are highlighted. In order to identify forms of Christian activism of individuals, denominations and evangelical benches, a gathering was realized of 972 bills distributed among 22 parliamentarians, 631 proposed by state deputies and 341 by city councilors. These bills were classified by type of individual or collective authorship, stage of legal procedure and legislative intervention area: public administration; denomination of own public; human rights; education; sport and leisure; evangelical corporate interests; trade, industry and services; environment; historical heritage and culture; public health; public security; work, employment and income; traffic and transport; tributes; public utility. The contextual approach of socio-biographical trajectories, profiles of parliamentary acting, institutional, ecclesiastical and doctrinal shades of the evangelical denominations, as well as of involvement in the production and propagation of public controversies about education, gender and secularity, intends to offer empirical and interpretative subsidies to potential comparisons with other regions, states, Brazilian cities and transnational experiences. In addition, it aims to contribute to sociological investigations concerning forms of Christian activism in the legislative power and in public controversies, based on the Minas Gerais and Belo Horizonte contexts, during the process of agonistic, relational and pluralistic construction of the democratic constitutional state and new participatory and representative forms of the religious in the public sphere.